Eltrombopag and its beneficial role in management of ulcerative Colitis associated with ITP as an upfront therapy case report - Elabbass A. Abdelmahmuod (14777296) (2023)
Eltrombopag can be used safely as upfront medication in the management of ulcerative colitis as well as ITP, and it showed a beneficial effect in both disorders. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3783